2022
DOI: 10.3390/diagnostics12061343
|View full text |Cite
|
Sign up to set email alerts
|

Translation of a Protease Turnover Assay for Clinical Discrimination of Mucinous Pancreatic Cysts

Abstract: The classification of pancreatic cyst fluids can provide a basis for the early detection of pancreatic cancer while eliminating unnecessary procedures. A candidate biomarker, gastricsin (pepsin C), was found to be present in potentially malignant mucinous pancreatic cyst fluids. A gastricsin activity assay using a magnetic bead-based platform has been developed using immobilized peptide substrates selective for gastricsin bearing a dimeric rhodamine dye. The unique dye structure allows quantitation of enzyme-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The peptide substrate is adapted from a previously identified 3CL protease cleavage sequence before NSP7 in the polyprotein (ATLQAIAS), an N-terminal dimeric dye to enable assay readout, and a C-terminal biotinylated lysine for immobilization to magnetic beads [33,36]. The lysine-biotin residue is separated from the rest of the peptide by serine-diethylene glycol spacer to preserve the biotin-streptavidin complex [35,40]. After immobilization on streptavidin-conjugated blocked magnetic beads, the unbound substrate is washed away using an excess Buffer I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptide substrate is adapted from a previously identified 3CL protease cleavage sequence before NSP7 in the polyprotein (ATLQAIAS), an N-terminal dimeric dye to enable assay readout, and a C-terminal biotinylated lysine for immobilization to magnetic beads [33,36]. The lysine-biotin residue is separated from the rest of the peptide by serine-diethylene glycol spacer to preserve the biotin-streptavidin complex [35,40]. After immobilization on streptavidin-conjugated blocked magnetic beads, the unbound substrate is washed away using an excess Buffer I.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic procedures for the dimeric rhodamine 6G dye used in the present study have been reported previously [34,35]. This dye was coupled to the N-terminus of resinbound biotinylated peptides, prepared using a liberty blue synthesizer (CEM, Matthews, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this review have translated assays using Raman-active dyes that have shown detection limits below those of traditional fluorescence measurements ( 71 ). Furthermore, Suresh et al have published the first example of translating a SERS assay for protease activity of gastricsin to a clinically ready platform with a small cohort of human pancreatic cyst fluid samples ( 72 ). Pancreatic cyst fluid is a notoriously tricky medium with which to run assays or optically quantify results, and the simplest solution is significant sample dilution to diminish interfering substances.…”
Section: Advanced Research Geared Toward Clinical Translationmentioning
confidence: 99%
“…PASSOnline is a database for predicting the bioactivity of organic compounds based on the analysis of the structure-activity relationships of more than 300,000 organic compounds as a training set, which has an average accuracy of above 95 % [11]. The bioactivities selected were gastrin inhibition, gastritis treatment [12], inhibition of gastric secretion [13], and gastricsin inhibition [14].…”
Section: Screening-based Probable Bioactivity Analysismentioning
confidence: 99%